2016
DOI: 10.1177/1098612x16645142
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and pathogenesis of cranial cruciate ligament rupture in cats by histological examination

Abstract: Objectives The aim of this study was to examine histologically intact and ruptured cranial cruciate ligaments in cats, in order to evaluate whether degeneration is a prerequisite for rupture. Methods We performed a histological examination of 50 intact and 19 ruptured cranial cruciate ligaments in cadaver or client-owned cats, respectively, using light microscopy. Cats with stifle pathology were further divided into five age groups in order to investigate the relationship of changes in the ligament with lifesp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…The age of the cats in our study is comparable to earlier reports, 6,14,17 and the weight is similar to that of randomly selected healthy controls in two earlier studies of CCLD in cats. 5,6 A greater proportion of cats in our study was insured vs the general insurance coverage (35.7% in 2012) of cats in Sweden. 28 This discrepancy in insurance coverage could indicate that owners of insured cats are more likely to seek veterinary advice in cases of CCLD.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The age of the cats in our study is comparable to earlier reports, 6,14,17 and the weight is similar to that of randomly selected healthy controls in two earlier studies of CCLD in cats. 5,6 A greater proportion of cats in our study was insured vs the general insurance coverage (35.7% in 2012) of cats in Sweden. 28 This discrepancy in insurance coverage could indicate that owners of insured cats are more likely to seek veterinary advice in cases of CCLD.…”
Section: Discussionmentioning
confidence: 70%
“…A degenerative process in the ruptured CCL has been reported in dogs, 30,31 and there is an ongoing discussion about the aetiology of CCLD in cats. 5,6 A recent study by Wessely et al 5 found no histological evidence of a degenerative process in the CCL of cats, while a study by Harasen 6 supported both a traumatic and a degenerative aetiology of the disease. However, only a single CCL was examined histologically in the latter study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cranial cruciate ligament (CrCL) rupture is reported far less commonly in cats than in dogs. 1 Potential explanations for this include the CrCL being larger than the caudal cruciate ligament in cats, 2 4 the lower amount of differentiation of fibrocartilage in the cat 5 and the potential for many cats with CrCL rupture never being evaluated by a veterinarian. 2 Historically, a traumatic event has been assumed to be the main cause for CrCL rupture in cats; 1 , 6 however, the actual cause is not entirely clear in every case.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Indeed, a recent study showed that up to 14% of cats appear to develop bilateral disease. 11 In addition, although one study 5 failed to confirm any histologic evidence of degeneration as a contributing factor to CrCL rupture, other studies have demonstrated the presence of degenerative changes such as calcification in the CrCL prior to complete rupture, 12 and moderate-to-severe stifle osteoarthritis (OA), despite an acute onset of lameness. 13 These latter findings would tend to support a degenerative process in at least a subset of cats with CrCL injury.…”
Section: Introductionmentioning
confidence: 99%